2015
DOI: 10.1590/s0004-28032015000200015
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Her2 in Adenocarcinoma of the Stomach

Abstract: -Background -Worldwide, gastric cancer is the fourth cancer in incidence and the second most common cause of cancer death. Gastric cancer is asymptomatic in the early stages and very often diagnosed at advanced stages, determining a dismal prognosis. Expression of the HER2 gene has been identified in about 20% of gastric cancer cases, and its hyper-expression is associated with poor prognosis. Objective -To investigate HER2 immunohistochemical expression in gastric adenocarcinoma and its relationship to the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
12
1
1
Order By: Relevance
“…However, the grading score for breast cancer was used for HER2 status assessment, in which the entire cell membrane should be stained, and not only lateral or basolateral walls, which suggests underestimation of HER2 positivity. In more recent research using specific HER2 scoring criteria for GC, IHC 3+ cases ranged from 0.8 % to 11.6 % [ 19 22 , 25 , 26 ]. Studies showing the lowest rates (0.8 %, 3 % and 6 %) used tumor tissue microarrays (TMAs) obtained from surgical specimens and other anti-HER2 antibodies rather than 4B5 [ 19 , 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the grading score for breast cancer was used for HER2 status assessment, in which the entire cell membrane should be stained, and not only lateral or basolateral walls, which suggests underestimation of HER2 positivity. In more recent research using specific HER2 scoring criteria for GC, IHC 3+ cases ranged from 0.8 % to 11.6 % [ 19 22 , 25 , 26 ]. Studies showing the lowest rates (0.8 %, 3 % and 6 %) used tumor tissue microarrays (TMAs) obtained from surgical specimens and other anti-HER2 antibodies rather than 4B5 [ 19 , 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large systematic review including data from 49 studies found a median rate of 18 % of HER2 positivity in 11,337 patients with GC [ 18 ]. Nevertheless, the prevalence of HER2-positive cases among Brazilian patients remains unknown, with few data published [ 19 26 ]. Since the Brazilian public health system has not yet endorsed the use of TZB for GC treatment in this country, we believe that the detection of HER2-positive GC in Brazilian patients may provide scientific basis for the establishment of new public health policies and define better clinical protocols to improve treatment of these patients in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Such nding is similar to those of various other studies from American and European researchers who have reported gastric cancer HER2 protein positive rates ranging from 10 to 22.8% 4,5 . However, some Asian studies have reported rates ranging from 11.7 to 15.74% 14,19,20 . The importance of the HER2 protein status in GC remains controversial and more and more researchers are studying the signi cance of HER2 protein expression in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in such studies the HER2 protein expression status was measured by immunohistochemistry (IHC) and the (normal, deletion or ampli cation) status was evaluated by uorescence in situ hybridization (FISH) analysis; those patients with IHC 3+ or IHC grade 2+ and FISH+ were considered HER2 protein overexpression. Recently, several studies reported the clinical characteristics and prognosis relating with HER2 protein overexpression in GCs 2,13,14 . However, the conclusions drawn from such studies were varied.…”
Section: Introductionmentioning
confidence: 99%
“…Although trastuzumab in combination with chemotherapy can prolong the survival of patients with HER2-positive advanced gastric cancer, 3–5 several studies show that the HER2-positive rate of gastric cancer patients in China is only around 12%–13%. 6 , 7 The role of chemotherapy is still of paramount importance in treatment of HER2-negative gastric cancer. In a sense, chemotherapy can prolong the survival time and improve the life quality of these patients, 8 but the response rate of first-line chemotherapy for advanced gastric cancer patients is no more than 50%, and the median overall survival (mOS) is about 13 to 16 months, 9 , 10 which is not expected in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%